STOP5: a hot debrief model for resuscitation cases in the emergency department - Walker, Craig Andrew (Clin Exp Emerg Med, 2020)
OBJECTIVE: Team-based resuscitation in emergency departments (EDs) is an excellent opportunity for hot debriefs (HDBs). In creating a bespoke HDB model for emergency medicine resuscitations, we sought to optimize learning from clinical experience, identify team strengths, challenges, encourage honest reflection and focus on ways of improving future performance. METHODS: Multidisciplinary ED focus groups reviewed existing models, identified benefits/barriers and created new frame works, testing and adapting further using fottage of a simulated complex resuscitation case. The new HDB tool was coined: “STOP5” (STOP for 5 minutes). Cases targeted were prehospital retrievals, major trauma, cardiac arrests, deaths in resuscitation, and staff-triggered. The framework details included a specifically scripted introduction followed by core elements that were S: summarize the case; T: things that went well; O: opportunities to improve; P: points to action and responsibilities. Staffs were surveyed at 1 month prior then 6 and 18 months post-introduction. Data collection forms were used to identify and track hard outcomes/system improvements resulting directly from HDBs. RESULTS: Potential benefits identified by respondents included: improved staff morale; team cohesion; improved care for future patients; promoting a culture for learning, patient safety and quality improvement. Ten process and equipment changes resulted directly from STOP5 over 12 months. CONCLUSION: We anticipate the STOP5 framework to be globally generalizable and effective for many ED teams.